2011
DOI: 10.1183/09031936.00159111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary exacerbations on long-term lung function decline in cystic fibrosis

Abstract: ABSTRACT:It is unknown what proportion of long-term lung function decline in cystic fibrosis (CF) is explained by pulmonary exacerbations. The aim of this study was to determine how exacerbations requiring hospitalisation contribute to the course of CF lung disease.This was a retrospective cohort study. The primary outcome was the rate of decline of forced expiratory volume in 1 s (FEV1) % predicted.Out of 851 subjects, 415 (48.8%) subjects had o1 exacerbation. After adjustment for confounders, the annual rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
159
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(177 citation statements)
references
References 25 publications
9
159
1
8
Order By: Relevance
“…This finding is not surprising, as many CF deaths are preceded by worsening infection; however, minimising these events is critical, as the rate of decline in FEV1 is greatest when exacerbations occurs frequently and within a short time frame [26]. Malnutrition continues to be an important risk factor for death.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is not surprising, as many CF deaths are preceded by worsening infection; however, minimising these events is critical, as the rate of decline in FEV1 is greatest when exacerbations occurs frequently and within a short time frame [26]. Malnutrition continues to be an important risk factor for death.…”
Section: Discussionmentioning
confidence: 96%
“…In a study of asthmatics over a period of 11 years, a relationship was seen between exacerbation frequency and FEV1 decline [8]. In a Canadian study, WATERS et al [9] showed that severe cystic fibrosis exacerbations (requiring hospitalisation) were associated with greater FEV1 decline. Although the European Cystic Fibrosis Society study did not report on exacerbations they have reported a link between chronic Pseudomonas aeruginosa infection (a known risk factor for cystic fibrosis exacerbations) and FEV1 decline [10], from which such a relationship may be inferred and this supports the findings of the Canadian study.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Without intervention, this situation gradually deteriorates causing plugging of small airways, bacterial infection, chronic local inflammation and eventually bronchiectasis [9,19,21]. Furthermore, repeated pulmonary exacerbations in CF have been shown to contribute to an accelerated decline in lung function [33].…”
Section: Review: Cftr Modulators In Cf N Derichsmentioning
confidence: 99%